Volatile organic compounds conversion pathways and odor gas emission characteristics in chicken manure composting process - Jiang, Yan; Yao, Yanying; Liu, Haolang; Zhang, Shengmin; Bai, Xin; Ma, Xiulan; Wang, Yujun; Ren, Qibiao (Frontiers in Ecology and Evolution, 2023)
Composting is a highly effective method for managing the growing quantity of agricultural waste, promoting nutrient recycling, and advancing sustainable agriculture. However, the significant amounts of volatile inorganic compounds (VICs) and volatile organic compounds (VOCs) generated during the composting process cannot be ignored due to their serious environmental hazards and detrimental impact on human health. The types and pathways of VICs and VOCs produced during the composting process remain not well understood. In this study, we investigated the VOCs produced during chicken manure and straw composting using gas chromatography-mass spectrometry (GC/MS). We performed qualitative and quantitative analyses of VOCs in composting emissions gases and their correlation with odor. Our results showed that 44 VOCs were detected during composting, including 4 oxidation-containing compounds, 2 sulfur-containing organics, 5 alkanes, 19 halogenated compounds, and 14 aromatic compounds. Aromatic compounds were found to be the main component of VOCs, accounting for 59.14% of the total content. The highest VOC content was found in the pre-composting period, and the highest emitting VOC was p-Isopropyl Toluene, which reached 7870.50 μg/m3. We identified eight substances that were highly correlated with odor concentration (p<0.01) and are the main odor-causing substances that need to be monitored and controlled. Our study provides important insights into the transformation of volatile gases during the composting process. It highlights the need for proper management practices to control VOCs emissions and reduce their environmental impact.